ANALISIS DEBIT PUNCAK DAS PADANG GUCI KABUPATEN KAUR PROVINSI BENGKULU - Khairul Amri; Ahmad Syukron (Jurusan Teknik Sipil Universitas Bangka Belitung, 2014)
This research aims to determine how much the peak discharge (maximum) discharge that occurred in the catchment area Padang Guci of regency Kaur province Bengkulu. by analyzing the rainfall data. The method of rainfall analysis with Melchior method is a statistical analysis of the hydrology in a way that aims to predict the peak (maximum) discharge with the specific time return. Estimation of the peak (maximum) discharge in this manner using the maximum daily rainfall data for 20 years to be analyzed in stages starting from the calculations Statistical Parameter, Determination of Distribution Type, Test Match Distribution, Rainfall Design, to obtain the value of Time of Concentration (Tc). The exact distribution pattern to the rainfall data was Log Person III. From the research that has been done, for over 2 years old at the time the maximum discharge in the catchment area Padang Guci at 162,957 m3/second.